2010
DOI: 10.1108/03321641011044532
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of small power transformer

Abstract: PurposeThe purpose of this paper is to present a methodology of identification and calculating vibrations of power transformers caused by magnetostriction.Design/methodology/approachAll calculations are based on finite element approach. Electromagnetic model uses 2D time stepping solution in nonlinear continuum of the core accompanied with equivalent representation of overlapping areas. Structural model is 3D with special representation for laminated core limbs. Theoretical results are compared with experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…With the deepening of research, scholars have found that the direct causes of transformer vibration and noise mainly include the following aspects: first, core vibration caused by magnetostriction of silicon steel sheet; second, core vibration caused by electromagnetic attraction; third, vibration caused by magnetic leakage; and fourth, DC bias has influence of on transformer noise. 6,7 Among them, the magnetostriction effect of silicon steel sheet is an important cause of transformer vibration. Scholars have carried out various researches on the vibration of silicon steel sheet due to the magnetostriction effect, including modeling, theoretical derivation, analysis and calculation, and experiments.…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of research, scholars have found that the direct causes of transformer vibration and noise mainly include the following aspects: first, core vibration caused by magnetostriction of silicon steel sheet; second, core vibration caused by electromagnetic attraction; third, vibration caused by magnetic leakage; and fourth, DC bias has influence of on transformer noise. 6,7 Among them, the magnetostriction effect of silicon steel sheet is an important cause of transformer vibration. Scholars have carried out various researches on the vibration of silicon steel sheet due to the magnetostriction effect, including modeling, theoretical derivation, analysis and calculation, and experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their acoustic parameters have become almost as important as the classic exploitation ones (Girgis et al , 2008). The noise coming from the load current usually dominates the no-load emission originated from the magnetostriction phenomena (Kubiak and Witczak, 2010) appearing in the transformer core. The contribution to the load noise created by windings alone is usually estimated by the empirical relationships (Lukic et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous researches [8], the MS behavior of silicon steel materials follows piezomagnetic laws which is rewritten as:…”
Section: Functional Energy Of Coresmentioning
confidence: 99%
“…Several papers have analyzed the vibration of cores due to magnetostrictive effect in 2D, some based the Principle of virtual work [3], and others based the equations of elasticity method in a similar way as thermal stresses [4][5][6]. The aim of this paper was to investigate a feasible way to determine the operating point of transformer cores within the vibration noise limit set by the government.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation